Linking Sociocultural Differentiated Instruction With Motivation and Higher-Order Thinking in Indonesia EFL Classrooms - Muhamad Yahrif; Sabaruddin Sabaruddin; Suharti Siradjuddin (Jurnal Pendidikan Bahasa Inggris Undiksha, 2026)
This study examines the relationship between Sociocultural-Based Differentiated Instruction (SCDI), student motivation, and higher-order thinking skills (HOTS) in Indonesian EFL classrooms within the Merdeka Belajar curriculum. While differentiated instruction has been widely implemented to address learner diversity, empirical evidence linking sociocultural differentiation with motivation and higher-order thinking in EFL contexts remains limited. Employing a convergent parallel mixed-methods design, quantitative data were collected from 184 junior high school students through a Likert-scale questionnaire, while qualitative insights were obtained from in-depth interviews and focus group discussions involving 8 English teachers and 8 students from two public schools. Quantitative findings revealed strong positive correlations between sociocultural-based differentiation, students’ motivation and engagement, instructional relevance, learning outcomes, and higher-order thinking skills (r = 0.60–0.74, p < .01). An independent-samples t-test further indicated a significant difference in perceived relevance and adaptation across school contexts (p < .05). Qualitative findings corroborated these results, demonstrating that culturally grounded instruction enhanced learner identity, participation, and critical reflection. The study contributes a conceptual and empirical linkage between sociocultural differentiation and higher-order learning processes in EFL classrooms. The findings offer pedagogical implications for culturally responsive teaching practices and EFL teacher development under the Merdeka Belajar framework. Therefore, the purpose of this study is to examine how Sociocultural-Based Differentiated Instruction (SCDI) influences students’ motivation, learning relevance, learning outcomes, and higher-order thinking skills, as well as to explore teachers’ experiences in implementing SCDI within English language classrooms under the Merdeka Belajar curriculum.